Perbandingan Luaran Lulusan Pendidikan Teknik Elektro dengan Non-Kependidikan - Atikah Zulfianti Putri; Riki Mukhaiyar (Ranah Research : Journal of Multidisciplinary Research and Development, 2021)
In this study, the authors compared the achievement of the quality of graduates of the Electrical Engineering Education study program and non-educational Electrical Engineering, and this research was conducted on graduates of the Electrical Engineering Education study program at UNP and Electrical Engineering non-educational at Andalas University. The type of research used was a literature study, study research procedures The literature has four stages, namely data collection, data analysis, and results. From the results of the research that has been done, the curriculum for Electrical Engineering Education at Padang State University and the non-Electrical Engineering Education curriculum at Andalas University have differences. Where the Electrical Engineering Education curriculum at Padang State University is more directed at the quality of graduates to work in the world of education while the non-Electrical Engineering Education curriculum at Andalas University is more directed at the quality of graduates to work in the industrial world.